2019
DOI: 10.1186/s40813-019-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

How effective are clinical pre-farrowing risk assessment and the use of soft rubber mats in preventing shoulder ulcers in at-risk sows?

Abstract: Background Lameness, low BCS and scar tissue in the skin covering the tuber spina scapulae are known as risk factors for shoulder ulcer in sows. In a two-step study, the predictive ability of pre-farrowing clinical examination and the preventive effect of rubber mats on the development of shoulder ulcers in at-risk sows were evaluated. Material and methods The study included 659 sows that were clinically examined one week before farrowing to distinguish risk sows from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
(17 reference statements)
2
6
0
Order By: Relevance
“…Finally, 2% of the sows entered farrowing with shoulder lesions, and 24% of them had a shoulder lesions at weaning with no differences between treatments. Our results are similar to those of Meyer et al [ 15 ] where the prevalence of shoulder lesions was 23% in sows defined as non-at-risk to develop this condition, after 3 weeks of lactation, in closed crates. Other studies have shown a lower prevalence of shoulder lesions (around 14%) in the same lactation time period [ 6 , 29 ], independent of the housing system where the sow was being kept.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, 2% of the sows entered farrowing with shoulder lesions, and 24% of them had a shoulder lesions at weaning with no differences between treatments. Our results are similar to those of Meyer et al [ 15 ] where the prevalence of shoulder lesions was 23% in sows defined as non-at-risk to develop this condition, after 3 weeks of lactation, in closed crates. Other studies have shown a lower prevalence of shoulder lesions (around 14%) in the same lactation time period [ 6 , 29 ], independent of the housing system where the sow was being kept.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have shown a lower prevalence of shoulder lesions (around 14%) in the same lactation time period [ 6 , 29 ], independent of the housing system where the sow was being kept. There are a lot of environmental and animal-related risk factors for shoulder lesions in sows [ 30 ] and the three most relevant sow-related risk factors are BCS, lameness, and parity [ 15 ]. Since we blocked by parity, and BCS and lameness were not different between treatments, our results agree with these previous studies where confinement duration is not a risk factor for shoulder lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sows developing shoulder lesions, or shoulder sores, after farrowing is a well-known condition that has been reported in up to 50% of animals on some farms [1,2] and is widely considered to be a multifactorial problem. While there appears to be consensus about certain risk factors for lesion development, such as a low body condition score [2][3][4][5], other predisposing factors may include breed, parity, and weaning weight [5]. The development of a shoulder sore can result in economic losses for producers as treatments are limited and sows with severe lesions often have their piglets weaned early, consequently negatively impacting the litter.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond this, however, little is understood about how the lesions progress and heal. Some studies have demonstrated how different treatment choices can alter the rate of healing [5,8], with rubber mat flooring appearing to be an effective feature of treatment plans [4,5]. However, to our knowledge, no studies have examined the daily changes lesions undergo throughout the development and healing process.…”
Section: Introductionmentioning
confidence: 99%